The Effectiveness Test of Trichoderma harzianum, Mycorrhiza and Bacteria B8 on the Growth of Phytophthora nicotianae in Pineapple Plants (Ananas comosus L. Merr) at PT.Great Giant Pineapple - Larasati, Candra Violita; Syamsulhadi, Mochammad; Widjayanti, Tita (Journal of Tropical Plant Protection, 2023)
This study aims to determine the potential of biological agents to inhibit the pathogen P.  nicotianae that causes liver rot and the effect of biological agents on the growth of pineapple plants at PT. Great Giant Pineapple. The research was carried out at the Experimental Field and Research and Development Protection Laboratory of PT. Great Giant Pineapple, Terbanggi Besar, Central Lampung from September to November 2022. The research was carried out in several stages, namely the preparation stage and the implementation stage. The preparation stage includes land preparation, breeding and application of T. harzianum, preparation of liquid culture of T. harzianum and B8 bacteria, dipping crowns, and selection of crowns and tagging. While the implementation phase includes planting, application of T. harzianum, mycorrhiza, and B8 bacteria, observation of disease occurrence level, antagonist test, observation of new leaf growth, and plant observation. The data obtained were analyzed using the T-test, which compared the control plot with the treatment plot (T. harzianum, mycorrhiza, and B8 bacteria). The results showed that the application of the biological agent T. harzianum had a significant effect on suppressing the pathogen P. nicotianae that causes heart rot in pineapple plants in vitro. In addition, the application of T. harzianum, mycorrhiza, and B8 bacteria significantly affected the growth of the number of tillers, d-Leaf height, and d-Leaf index.